Pengaruh Quick Ratio, Inventory Turnover, Fixed Assets Turnover, dan Assets Turnover terhadap Profitabilitas Perusahaan Sektor Farmasi di BEI Tahun 2016-2018 - Umar Hamdan; Lailatul Maufiroh (IAIN Madura, 2022)
The current rapid development of the world economy is marked by advances in technology and the growth of innovation that continuously makes business competition more competitive. Business people are starting to realize that the ability to compete does not only lie in the ownership of the company's tangible assets, but also in innovation, information systems, organizational management and organizational resources owned by the company. This study uses a quantitative approach. The data used in this study is secondary data obtained from the annual financial statements, with a sample of 10 companies and the 2016-2018 period, so the data is 30. The analytical methods in this study are data normality test, autocorrelation test, heteroscedasticity test, test multicollinearity, multiple linear regression, hypothesis testing and coefficient of determination test. This study shows that the F Quick Ratio test, Inventory Turnover, Fixed Asset Turnover and Asset Turnover have a significant effect on the ROA of pharmaceutical sector companies listed on the IDX for the 2016-2018 period. While partially Quick Ratio, Inventory Turnover, and Asset Turnover have a significant effect on the ROA of pharmaceutical sector companies listed on the IDX for the 2016-2018 period.